Towards a Sustainable Circular Economy - Remarks on plastics and wood-waste sector - Markus Will (The Central European Review of Economics and Management (CEREM), 2019)
Aim: As the traditional approach towards entering a path of sustainabe development based on a "efficiency, consistency, sufficiency aproach" is questionable, This article discusses opportunities and challenges for the circular economy to become a "last chance" fort he current capitaist system to become more sustainable.Design / Research methods: Two case studies of material (waste) streams of plastics and wood-waste are presented in order to identify challenges in the development and functioning of the circular economy. Conclusions / findings: While the circular economy can deal with threats to sustainability embraced in an efficiency and sufficiency approach, it refers to a technology-driven consistency approach, not questioning the consumption and production patterns in the capitalist economy, and the functioning of the market economy as such.
Keywords: 330